Perbedaan Kadar Ureum Kreatinin Pada Penderita Gagal Ginjal Kronis Sebelum dan Sesudah Hemodialisa Di Rumah Sakit Wijaya Kusuma Purwokerto - Herowati, Nunuk; Widyayanti, Oksita Asri; Mohtar, Cici Farhana Ambarwaty (Universitas Mohammad Husni Thamrin, 2025)
Chronic kidney failure (CKF) is a progressive and fatal disease in which the kidneys are no longer able to maintain metabolism, fluid and electrolyte balance Chronic Kidney Failure if the GFR value is <60ml/minute, the prevalence of Chronic Kidney Failure (CKF) worldwide has increased by 2.3%. The incidence of Chronic Kidney Failure (CKF) in Indonesia is 0.38% of the total population of Indonesia. Hemodialysis is a blood filtration treatment method used to remove fluids and waste that accumulate in the blood and cause poisoning when the kidneys experience serious disorders or gradually cannot function. The purpose of this study was to determine the difference in creatinine urea levels in patients with chronic kidney failure (CKF) before and after hemodialysis at the Level III Hospital 04.06.01 Wijaya Kusuma Purwokerto. This study used a quantitative descriptive method, with a sample size of 64 people. Data analysis was carried out using SPSS with a paired sample test. The results of the urea level study obtained an average urea level in patients of 155.34. The minimum value obtained was 72 and the maximum value was 273. The urea level after hemodialysis obtained an average of 95.92. The minimum value was 43 and the maximum value was 273. The creatinine level before hemodialysis obtained results where the average was 36.82, the minimum value was 2.23 and the maximum value was 14.10. The average creatinine level after hemodialysis obtained a minimum value of 1.33 and a maximum of 14.10 with an average of 7.29. The conclusion is that there is a significant difference in urea and creatinine levels before and after hemodialysis with the results of statistical tests obtained a value of p = 0.000. Keywords: Acute Renal Failure, Chronic Renal Failure, Hemodialysis, Creatinine, Urine